Evidence of vancomycin-resistant Staphylococcus aureus, multidrug-resistant S. aureus, and Enterococcus faecium-causing mastitis in Thailand and Cambodia - Sambo Na; Montira Intanon; Anyaphat Srithanasuwan; Wasana Chaisri; Witaya Suriyasathaporn (Veterinary World)
Background and Aim: Bovine mastitis, an inflammatory condition of the mammary gland, is a critical economic issue in the dairy industry. Antimicrobial resistance (AMR) to mastitis-causing pathogens poses a significant threat to dairy operations in Thailand and Cambodia. This study investigates the AMR of mastitis pathogens in Thailand and Cambodia. It focuses on detecting methicillin-resistant Staphylococcus aureus, vancomycin-resistant S. aureus (VRSA), and vancomycin-resistant enterococci by identifying the presence of mecA, vanA, and vanB genes in bacterial isolates.